Variational quantum simulation of ultrastrong light-matter coupling - Agustin Di Paolo; Panagiotis Kl. Barkoutsos; Ivano Tavernelli; Alexandre Blais (Physical Review Research, 2020)
We propose the simulation of quantum-optical systems in the ultrastrong-coupling regime using a variational quantum algorithm. More precisely, we introduce a short-depth variational form to prepare the ground state of the multimode Dicke model on a quantum processor and present proof-of-principle results obtained using an IBM device. We moreover provide an algorithm for characterizing the ground state by Wigner state tomography. Our work is a first step toward digital quantum simulation of light-matter systems with potential applications to few-impurity spin-boson models.